Local acceleration effects of adatom at the vicinity on the surface: Case of Co nano thin-films on Al surface - Kim, Sang-Pil; Lee, Seung-Cheol; Lee, Kwang-Ryeol; Chung, Yong-Chae (TRANS TECH PUBLICATIONS LTD, 2006)
The local acceleration effects, which are peculiar phenomena during atomic scale deposition process, were investigated by Molecular Dynamics (MD) simulation. The values of local acceleration were distributed widely for various surface orientations. Deposited atoms were accelerated along the potential energy surface, and accelerated values were evidently dependent on the local configuration of the surface. In contrast, the local acceleration became negligibly small for clusters consisting of many atoms.
Keywords: MOLECULAR-DYNAMICS; METALS